(3EOGQI GdCYeGd GdOhdjI hGdYGdejI (B/s - (3GdMQjQj, eMeO SQhQs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2012)
(3eONd YGe dEOGQI GdCYeGd GdOhdjI hGdYGdejI GdeYGUQI hGdMOjKI , GdeOGQS GdEOGQjI , GdhXGFa GdEOGQjI GdMOjKI aj efXeGJ GdCYeGd GdOhdjIs
(3GdeQGLY U(B.207s
Keywords: (3EOGQI GdCYeGds; (3GdefXeGJ GdOhdjIs; (3efXeI GdYed GdOhdjIs